THE STYLISTIC DEVICES ON CHIILDREN' SONGS IN COCOMELON YOUTUBE CHANNEL - Rahmaditya Khadifa Abdul Rozzaq Wijaya; Wijaya Heru Santoso (Universitas Duta Bangsa Surakarta, 2021)
This research is a stylistic study that examines the use of stylistic tools. These tools are (1) figure of speech, (2) sound play or onomatopoeia, and (3) diction. The purpose of this research is to describe the use of stylistic tools in the lyrics of children's songs on the Cocomelon Youtube Channel. The data in this study are in the form of words, phrases, clauses, or sentences that contain stylistic tools as mentioned above. The source of data in this study is the lyrics of children's songs on the Cocomelon Youtube Channel. Techniques for collecting data using listening and note-taking techniques. Furthermore, the data analysis technique was carried out by paying attention to and matching the data with the theory used as an approach.